Tales of the city - Maupin, Armistead 1944- (HarperPerennial, 1994)
The story of the residents of an apartment house at 28 Barbary Lane in San Francisco.
Keywords: City and town life -- Fiction; San Francisco (Calif.) -- Fiction; Fiktionale Darstellung; Humorous fiction